African Mitochondrial DNA Haplogroup L2 Is Associated With Slower Decline of β-cell Function and Lower Incidence of Diabetes Mellitus in Non-Hispanic, Black Women Living With Human Immunodeficiency Virus. (12th January 2020) - Sun, Jing; Brown, Todd T; Tong, Weiqun; Samuels, David; Tien, Phyllis; Aissani, Brahim; Aouizerat, Bradley; Villacres, Maria; Kuniholm, Mark H; Gustafson, Deborah; Michel, Katherine; Cohen, Mardge; et al.
Abstract: Background: Susceptibility to metabolic diseases may be influenced by mitochondrial genetic variability among people living with human immunodeficiency virus (HIV; PLWH), but remains unexplored in populations with African ancestry. We investigated the association between mitochondrial DNA (mtDNA) haplogroups and the homeostatic model assessments of β-cell function (HOMA-B) and insulin resistance (HOMA-IR), as well as incident diabetes mellitus (DM), among Black women living with or at risk for HIV. Methods: Women without DM who had fasting glucose (FG) and insulin (FI) data for ≥2 visits were included. Haplogroups were inferred from genotyping data using HaploGrep. HOMA-B and HOMA-IR were calculated using FG and FI data. Incident DM was defined by a combination of FG ≥ 126 mg/dL, the use of DM medication, a DM diagnosis, or hemoglobin A1c ≥ 6.5%. We compared HOMA-B, HOMA-IR, and incident DM by haplogroups and assessed the associations between HOMA-B and HOMA-IR and DM by haplogroup. Results: Of 1288 women (933 living with HIV and 355 living without HIV), PLWH had higher initial HOMA-B and HOMA-IR than people living without HIV. PLWH with haplogroup L2 had a slower decline in HOMA-B per year ( P interaction = .02) and a lower risk of incident DM (hazard ratio [HR], 0.51; 95% confidence interval [CI], .32–.82) than PLWH with other haplogroups after adjustments for age, body mass index, combination antiretroviral therapy use, CD4 cell counts, and HIV RNA. The impact of HOMA-IR on incident DM was less significant in those with haplogroup L2, compared to non-L2 (HR, 1.28 [95% CI, .70–2.38] vs 4.13 [95% CI, 3.28–5.22], respectively; P interaction < .01), among PLWH. Conclusions: Mitochondrial genetic variation is associated with β-cell functions and incident DM in non-Hispanic, Black women with HIV and alters the relationship between insulin resistance and DM. Abstract : Among women living with human immunodeficiency virus, African mitochondrial DNA haplogroup L2 was associated with a lower risk of diabetes mellitus; slower age-related declines in β-cell functions; and an attenuated impact of insulin resistance on incident diabetes mellitus.